Configurable Integrations: Configurable Integration of On‐Chip Quantum Dot Lasers and Subwavelength Plasmonic Waveguides (Adv. Mater. 21/2018). Issue 21 (May 2018) - Rong, Kexiu; Gan, Fengyuan; Shi, Kebin; Chu, Saisai; Chen, Jianjun
Abstract : By employing the dark‐field optical imaging technique with a position uncertainty of about 21 nm, Jianjun Chen and co‐workers from Peking University experimentally demonstrate the configurable integration of on‐chip quantum‐dot lasers and subwavelength plasmonic waveguides in article number1706546 . This configurable on‐chip integration with high flexibility and controllability will greatly facilitate the development of complex functional hybrid photonic‐plasmonic circuits.